A reassessment of human cranial indices through the Holocene and their implications for the peopling of South America. (February 2017) - Kuzminsky, Susan C.; Coonerty, Nina; Fehren-Schmitz, Lars
Abstract: South American populations have played a critical role in elucidating the timing, origin, and migration routes of the first Americans. Among the ongoing debates surrounding the peopling of South America, there has been a great deal of focus on the cranial shape of prehistoric populations on this continent, which some researchers have described as having two distinct forms. The cranial shape of early Holocene Paleoamericans, which predate approximately 8000 years BP, has been categorized as dolichocephalic (long-headed), while late Holocene populations have been generally described as brachycephalic (round-headed), despite more recent assessments that examine variation with a higher level of precision. Although more detailed analytical approaches to investigating craniofacial variation are available, researchers still categorize South American crania as having these two head shapes. These distinctions in head shape have been used to infer multiple origin models, some of which contend that the dolichocephalic population was biologically distinct and later replaced by brachycephalic individuals. In contrast, genetic studies infer a common ancestral origin among all prehistoric South American populations. Given discrepancies between genetic and cranial data, our study tests the hypothesis that Holocene populations consist of two cranial morphologies that coincide with the early and late Holocene periods. Using high-resolution 3D models generated from a laser surface scanner, cranial indices for 95 individuals from western South America dating from the Early, Middle, and Late periods were analyzed, most of which have been excluded from cranial assessments in South America. Our results show that the majority of crania analyzed in this study have an intermediate (mesocephalic) head shape, spatiotemporal variability, and no clear transition from dolichocephaly to brachycephaly during the Holocene. By re-examining the relevance of these categories that are determined through the calculation of the cranial index, and general morphological descriptions (long and narrow or short and wide skulls) that coincide with them, our research offers valuable insight into the ongoing debates centered on the colonization of South America. Given our results, we propose that caution should be used when referring to the terms "dolichocephalic" and "brachycephalic" head shapes and the general morphological descriptions for these terms to categorize early and late Holocene South American populations. Highlights: Cranial indices were computed for prehistoric western South American populations. Cranial variation is present despite genetic data showing common prehistoric ancestry. Dolichocephalic head shapes do decrease over time but do not disappear altogether.